Disparitas Regional Gagal Tumbuh pada Balita di Indonesia: Analisis CIAF dan E-CIAF dari SSGI 2022: Regional Disparities of Growth Failure among Children Under Five in Indonesia: Insights from CIAF and E-CIAF Analysis of SSGI 2022 - Suyatno, Suyatno; Kartasurya, Martha Irene; Fatimah, Siti; Nugraheni, Sri Achadi; Wijayanti, Lilis; Latifah, Hasna Izdihar (Amerta Nutrition, 2025)
Background: Growth failure among children under five years remains a key public health issue in Indonesia and requires appropriate measurement indicators. Conventional parameters such as stunting, wasting, or underweight might not adequately address the multidimensionality of malnutrition. Therefore, the Composite Index of Anthropometric Failure (CIAF) and the Extended Composite Index of Anthropometric Failure (E-CIAF) will provide a better, more detailed, and inclusive population-level representation of growth failure. Objectives: To determine the frequency of growth failure among Indonesian children under five based on CIAF and E-CIAF among the population and in a regionalized setting, and to identify the more sensitive indicator. Methods: Secondary data were obtained from the Indonesian Nutrition Status Survey (SSGI) 2022, which included 281,651 children (aged 0–59 months) in 34 provinces. Nutritional status was assessed using anthropometric failure classification by CIAF and E-CIAF. The difference in prevalence in different regions was ascertained by Chi-square testing, and significance was defined as a p-value<0.05. Results: E-CIAF had a higher rate of failure of Indonesian child growth than CIAF (27.0% vs 25.0%). Prevalence of non-Java-Bali kids was high as compared to the Java–Bali region (E-CIAF=28.1%, CIAF=26.9%). In the Eastern region of Indonesia, it had the high prevalence (E-CIAF) (32.0%, CIAF 30.8%). Conclusions: The finding suggested that E-CIAF is more sensitive than CIAF for assessing growth failure. The highest burden of this disease occurs outside Java Bali in Eastern Indonesia, stressing the importance of localized nutrition interventions.